PTAR Guide Book / Perpustakaan Tun Abdul Razak, UiTM - Perpustakaan Tun Abdul Razak, UiTM (Perpustakaan Tun Abdul Razak, UiTM, 2000)
Contains Mision, Vision, Objective, Introduction, Library Department, Library Collections, Facilities, Online Database, Library Intranet, Rules and Regulation, Classification System and Librarian's Directory.